D-Tagatose Feeding Reduces the Risk of Sugar-Induced Exacerbation of Myocardial I/R Injury When Compared to Its Isomer Fructose - Durante, Mariaconcetta; Sgambellone, Silvia; Lucarini, Laura; Failli, Paola; Laurino, Annunziatina; Collotta, Debora; Provensi, Gustavo; Masini, Emanuela; Collino, Massimo (Frontiers in Molecular Biosciences, 2021)
It is known that fructose may contribute to myocardial vulnerability to ischemia/reperfusion (I/R) injury. D-tagatose is a fructose isomer with less caloric value and used as low-calorie sweetener. Here we compared the metabolic impact of fructose or D-tagatose enriched diets on potential exacerbation of myocardial I/R injury. Wistar rats were randomizedly allocated in the experimental groups and fed with one of the following diets: control (CTRL), 30% fructose-enriched (FRU 30%) or 30% D-tagatose-enriched (TAG 30%). After 24 weeks of dietary manipulation, rats underwent myocardial injury caused by 30 min ligature of the left anterior descending (LAD) coronary artery followed by 24 h′ reperfusion. Fructose consumption resulted in body weight increase (49%) as well as altered glucose, insulin and lipid profiles. These effects were associated with increased I/R-induced myocardial damage, oxidative stress (36.5%) and inflammation marker expression. TAG 30%-fed rats showed lower oxidative stress (21%) and inflammation in comparison with FRU-fed rats. Besides, TAG diet significantly reduced plasmatic inflammatory cytokines and GDF8 expression (50%), while increased myocardial endothelial nitric oxide synthase (eNOS) expression (59%). Overall, we demonstrated that D-tagatose represents an interesting sugar alternative when compared to its isomer fructose with reduced deleterious impact not only on the metabolic profile but also on the related heart susceptibility to I/R injury.